Environment and resource policies for the world economy - Cooper, Richard N. (Brookings Institution, 1994)
In this book, part of the Brookings Integrating National Economies series, Richard N. Coopers evaluates the need for international policy action in natural resource and environmental management. Taking into account the diversity of individual states' circumstances and priorities, Cooper concludes that stiff environmental regulations generally are not the best answer to environmental management. He explains that developing countries are not likely to take actions to improve environmental hazards if those actions risk slowing their economic growth. Instead, policies that provide incentives for compliance with international standards are needed. The book outlines past international actions, what has worked and what has not, and provides recommendations for future action.
Keywords: Environmental policy.; Natural resources.; Environnement -- Politique gouvernementale.; Ressources naturelles.; environmental policy.; natural resources.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy.; Environmental policy; Natural resources; Milieubeleid.; Natuurlijke hulpbronnen.; POLITICAL SCIENCE / International Relations / General